Metode Penentuan Akad pada Transaksi Uang Elektronik - Sofwan Hadikusuma (ITB AAS INDONESIA Surakarta, 2021)
This paper is intended to explain the methods used by experts in determining the contracts used in electronic money transactions. The focus of this paper is not only on contract determination, but how a contract is embedded in electronic money transactions. This research is a qualitative research wich uses descriptive-analytic method. Data obtained from secondary sources such as books, journals, websites, and relevant documentation. The results showed that in principle, there are two methods in determining the contract in a muamalah transaction. The first method uses the editorial approach (words) which focuses on the contract words, and the second uses the substance (meaning) approach which considers the contract based on the aims and objectives of the contract as seen from the form of the agreement as well as the rights and obligations obtained by each party. Regarding the topic of discussion, it can be concluded that the determination of the contract in electronic money transactions uses a meaningful approach. That because the consideration used in determining the electronic money contract is based on the form of the transaction that occurs between the parties, not just the existing words.